Comparison of pulpal vitalization and root canal therapy in symptomatic immature permanent molars: Comparison between VPT (CEM and MTA) and RCT - Guang, Jianxia; Li, Junke; Guo, Shiling (Cellular and Molecular Biology, 2022)
Endodontic treatment of immature permanent teeth has various problems. Today, the primary goal in the treatment of such teeth is to preserve the life of the pulp so that roots can develop entirely and naturally. If vital pulp therapy can treat these teeth, the treatment will be simpler and less expensive. Therefore, this study compared vital pulp therapy (including calcium-enriched mixture (CEM) cement and MTA methods) and root canal therapy (RCT) in symptomatic immature permanent molars. Also, the expression of TLR-2 and TLR-4 was evaluated in the gingival tissue of patients for further evaluation. In this clinical trial study, 615 patients randomly received three treatments: pulpotomy with CEM (205 cases), pulpotomy with MTA (207 cases), and root canal therapy (203 cases). The presence of periapical lesion was evaluated radiographically at three-time points: start, six months, and 12 months after treatment. The expression of TLR-2 and TLR-4 was also evaluated in the gingival tissue of patients by the Real-time PCR technique. The one-year follow-up of the periapical index shows that the presence of periapical lesion at six-month follow-up in the three groups of MTA, CEM, and RCT equals 14 cases (8%), 7 cases (4%), and 40 cases (22%). The one-year follow-up equals 12 cases (7%), 9 cases (5%), and 33 cases (18%), respectively. The TLR-2 and TLR-4 gene expression results showed no statistical difference between the three groups (CEM, MTA, and RCT). Still, one year after treatment, there was a statistically different between vital pulp therapy (CEM and MTA) and root canal therapy (P<0.05). Also, the results showed no statistical difference between CEM and MTA treatment in terms of TLR-2 and TLR-4 gene expression before and one year after treatment. In general, the results showed that pulpotomy treatment using two biomaterials, CEM and MTA, is more successful than RCT treatment.